ABC analysis of anti cancer drugs in a tertiary care Employees’ State Insurance Corporation Hospital in Delhi - Narang, S.; Raju, S. K.; Kumar, R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Material management is co-ordinated activities comprising of planning, acquiring, storing and controlling the supply of various items for optimal use. Effective inventory management can bring about a substantial decrease in expenditure. ABC analysis categorizes all items based on their annual drug expenditure into three categories A, B and C for better control by different level managers. Methods: ABC analysis for anticancer drugs was done in ESIC Hospital, Basaidarapur which is a tertiary care hospital of ESI Corporation in Delhi. Total number of drugs analysed were 98 with total annual expenditure of Rupees 5.77 crores approximately. Results: 12.2% (n=12), 16.3% (n=16) and 71.4% (n=70) items were found to be in A, B and C categories respectively. Conclusions: ABC analysis identified the drugs which need more strict control by top level management. Inventory control techniques should be an integral part of any hospital store.